Maternal Outcome Pregnancy with Acute Hepatitis E Virus Infection (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine the maternal outcome in pregnant women with acute viral hepatitis caused by hepatitis E virus.Study Design: Case series.Duration of study: July 2012 to December 2012 fromSetting: Department of Obstetrics and Gynaecology Unit‐I, Sir Ganga Ram Hospital, Lahore.Material and Methods: A total of 100 cases fulfilling the inclusion/exclusion criterion were enrolled to determine the age distribution, gestational age, and the outcome in pregnant women with acute viral hepatitis caused by heoatitis E virus.Result: During the period of study, majority of the patients between 26‐30 years,i‐e,54% (n=54), means and SD was calculated as 28.43 +‐ 3.19 years, 48% (n=48) cases were between 37‐40 years of age, frequency of maternal outcome in pregnant women with acute viral hepatitis caused by Hepatitis E virus revealed 47% (n=47) with development of fulminant hepatic failure and 16% (n=16) had maternal mortality. Conclusion: The results of the study determined that adverse maternal outcome is higher among pregnant women with acute viral hepatitis E virus.
Keywords: Hepatitis E virus, Pregnant women, maternal outcome, Fulminant hepatic failure, Mortality.